(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Alice Walker’s The Color Purple exemplifies the transformative role of language in literature and life. This article explores how Walker’s deliberate lexical choices evoke emotional depth and enhance the narrative’s authenticity. Key aspects include the use of vernacular language to reflect Celie’s voice and context, emotionally charged word choices to capture her struggles and growth, and symbolic lexicon to underscore the novel’s themes of beauty, spirituality, and resilience. The shift in language from fragmented and oppressive to confident and joyful mirrors Celie’s journey of self-discovery and empowerment. Walker’s use of silence and unspoken words adds another layer of emotional intensity, highlighting the impact of trauma and healing. Through these linguistic techniques, The Color Purple transcends storytelling, offering a profound meditation on survival, transformation, and the enduring power of language to connect and inspire.